Does routine screening for breast cancer raise anxiety? Results from a three wave prospective study in England. Issue 4 (August 1995) - Sutton, S; Saidi, G; Bickler, G; Hunter, J
Abstract : OBJECTIVE–To investigate whether mammography raises anxiety in routinely screened women who receive a negative result. DESIGN–Prospective design in which women completed questionnaires at three key points in the breast screening process: at baseline (before being sent their invitation for breast screening), at the screening clinic immediately before or after screening, and at follow up, about nine months after baseline. Information was obtained from non-attenders as well as from attenders. SETTING–Bromley District Health Authority, served by the South East London Breast Screening Service. PARTICIPANTS–Two overlapping samples were used. Sample A comprised 1500 women aged 50-64 who were due to be called for first round screening at a mobile screening unit. Altogether 1021 (68%) returned a usable questionnaire and 795 of these (78%) also provided adequate information at nine month follow up: there were 695 attenders (including 24 women who received false positive results) and 100 non-attenders. Sample B consisted of 868 women who attended the screening unit in a three month period, 732 (84%) of whom provided adequate data. A total of 306 attenders (including 10 who received false positive results) occurred in both samples and provided adequate information on all occasions. The main analyses were based on these 306 women plus the 100 non-attenders. The analysis of retrospective anxiety took advantage of the larger sample size of 695 attenders. MAIN RESULTS–On average, the women were not unduly anxious at any of the three points in the screening process. Among attenders, there was no difference between anxiety levels immediately before and immediately after screening. Anxiety was lowest at the clinic and highest at baseline but the changes were very small in absolute terms. Anxiety did not predict attendance: there were no differences in anxiety levels between attenders and non-attenders at baseline. As expected, women who received false positive results recalled feeling extremely anxious after they had received the referral letter but their retrospective anxiety was also higher than in the negative screenees at earlier stages in the breast screening process. They also reported having experienced more pain and discomfort during the x ray. CONCLUSIONS–Anxiety does not seem to be an important problem in routinely screened women who receive a negative result. This finding is very reassuring in relation to a major criticism of breast screening programmes. Thus, apart from maintaining current procedures such as keeping waiting times to a minimum, there seems to be no need to introduce special anxiety reducing interventions into the national programme. On the other hand, the findings for women who received false positive results suggest that there are aspects of the experience of being recalled for assessment after an abnormal mammogram that warrant further attention. The relationship between contemporaneous and retrospective anxiety should also be studied.